MENUJU FAKULTAS DAKWAH DAN KOMUNIKASI IAIN BENGKULU (KAJIAN KEILMUAN DAKWAH YANG FAKULTATIF) - Rahmat Ramdhani (JURNAL ILMIAH SYI'AR, 2016)
Comprehensively  institutions development may interprented as one form of education reform offers to remedy campus organizing learning activities better and adequate for students. Autonomy in education is great potential for integration, interaction, connection and even intra-built scientific connections. Besides, practically also have an impact on enhancing performance, providing excellent service, and order administration. This spirit is the beginning of construction in welcoming the birth of the Faculty of Da’wa and Communication IAIN Bengkulu. In this article, the authors start from a historical perspective da’wah normatis scientific-theological to the practical- aplikated exposure to the study of propaganda facultative.